NUMERICAL MODELING OF THE PLANETARY BOUNDARY LAYER - Oliveira, P.; Soares, J.; Karam, H. A.; Pereira, M. M. R.; Marques Filho, E. P. (Revista de Engenharia Térmica, 2004)
This work describes the major available techniques to simulate the time and space evolution of the planetary boundary layer. For homogeneous and equilibrium conditions the structure of the planetary boundary layer can be diagnosed from the Monin-Obukhov, Free Convection, Local and Mixed Layer Similarity theories. For the other atmospheric conditions the planetary boundary layer can be numerically simulated using first and second order closure models and large eddy models. The closure models take into consideration the traditional statistical approach. Large eddy simulation models are based on the filtered equations of motion and require the statistical approach to estimate subgrid turbulence.